Cyber Crime in International Legal Instrument: How Indonesia and International Deal with This Crime? - Wijaya, Massulthan Rafi; Arifin, Ridwan (Universitas Negeri Semarang (UNNES), 2020)
Cybercrime is a new type of crime arising from globalization in this world. This crime is more dangerous than other crimes because the impact can cause world war. It is undeniable that this crime in the present has grown as time goes by until now, there are many cases of this crime. All countries compete to advance their technology for positive things, but many people abuse it for negative actions. We must be vigilant if we want to use technology because there are many bad people out there, if we are negligent then we can be affected by those bad people. Then the lack of public attention now that there is a new type of crime that is more dangerous than other crimes. We must protect each other so that we are not affected by cybercrime. This crime does not only have one sector but can be in all sectors, because this crime can be said to be an extraordinary crime.